PENGARUH NILAI PADA MATA KULIAH MATEMATIKA DASAR 1 DAN MATEMATIKA DASAR 2 DALAM MENYELESAIKAN SOAL HOTS MATEMATIKA PADA MAHASISWA PGMI UIN FATMAWATI SUKARNO BENGKULU - Selpia, Reni; Sagita, Rivana Puri; Cahyani, Apriana (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Knowing the influence of PGMI students ' scores in basic mathematics 1 and basic mathematics 2 in solving HOTS problems is the purpose of this study. The type of research applied is a quantitative method by taking samples from students of PGMI UIN Fatmawati Sukarno Bengkulu as many as 30 students. There are 2 independent variables in this study, namely the value of basic mathematics 1 and the value of basic mathematics 2 and 1 dependent variable is the value of solving the problem HOTS. The research instruments were questionnaire of course score and test of HOTS questions in the form of multiple choice questions of 10 items. In this study, it was found that the value of basic mathematics 1 and basic mathematics 2 had a positive and significant effect on the results of solving HOTS problems with a sig. value of 0.000<0.05 and a correlation coefficient of 0.946 which is included in the high category. So that the results obtained that if the value of basic math 1 and basic math value 2 is high, then the value of solving HOTS problems is also high and vice versa.